La necesidad de reformar la ley contra la violencia a la mujer y a la familia, en relación al nuevo proceso de juzgamiento - Sayay Lema, José Feliciano (2015)
This thesis started considering that the procedure for prosecuting breaches of domestic violence has been really outdated compared to the new oral procedures have been incorporated into other legislation Adjective law, such as the Code of Criminal Procedure Code Civil Procedure, Labour Code and to the Law itself Transit, Land Transport and Road Safety. As such and given the nature of the issues of domestic violence and women mainly, it is necessary to provide for expedited procedures, effective and full compliance with the constitutional provisions for the procedural system, this procedure must be oral and contemplate a procedure agile for flagrant violence should be tried immediately. Currently, the Government through the National Judicial Council has implemented Units Domestic Violence Court, there Judges and Family Judges will judge the violation of the rights of the family, but no procedure has been changed so therefore continue with the outdated structure of the old laws. In this research paper I managed to establish that it is very necessary to have a new procedure that including penalty and guarantees the rights of the victim and the perpetrator